The pre-conception maternal exposure to Sofosbuvir affects the mitochondrial biogenesis in prenatal fetal tissues: Experimental study on rats - Shimaa A. Mahmoud; Maryam M. Abdel-Aziz; Rana H. M. Khafaga; Hala A. Hafez; Maher A. Kamel; Sara A. Shaker (Molecular Medicine, 2023)
Abstract Background  Hepatitis C virus (HCV) infection is a global public health problem and Egypt has the highest HCV prevalence worldwide. Hence, global efforts target to eliminate HCV by 2030. Sofosbuvir is a nucleotide analogue inhibitor of HCV polymerase essential for viral replication. Animal studies prove that Sofosbuvir metabolites cross the placenta and are excreted in the milk of nursing animals. We aimed to investigate the possible effects of preconception maternal exposure to Sofosbuvir on mitochondrial biogenesis in prenatal fetal liver, skeletal muscle, and placental tissues. Methods  The study was conducted on 20 female albino rats divided into a control group receiving a placebo and an exposed group receiving 4 mg/kg orally/day for 3 months of Sofosbuvir. At the end of the treatment period, pregnancy was induced in both groups by mating with healthy male rats overnight. At gestational day 17, all pregnant female rats were sacrificed. Each fetus was dissected to obtain the fetal liver, skeletal muscle, and placental tissues. Results  The results of our study indicated that the exposure of young female rats to Sofosbuvir affects pregnancy outcomes. Fetal liver and muscle showed lower mitochondrial DNA-copy number (mtDNA-CN) by about 24% and 29% respectively, peroxisome proliferator-activated receptor-gamma coactivator-1 alpha and its downstream targets; nuclear respiratory factor-1 and mitochondrial transcription factor A. While the placental tissues showed different patterns, particularly elevated in mtDNA-CN by about 43%. Conclusions  The study provides preliminary evidence of the detrimental effects of Sofosbuvir on the pregnancy outcomes of the exposed females and may impair the placental and fetal organs’ development. These effects may be mediated through modulating mitochondrial homeostasis and functions.